ASUHAN KEPERAWATAN JIWA PSIKOSOSIAL PADA KLIEN YANG MENGALAMI BULLYING DENGAN MASALAH GANGGUAN ANSIETAS DI SMPK ST. ANTONIUS KALIPARE - Swito Prastiwi (Jurnal Keperawatan Terapan, 2023)
Anxiety is an emotional condition and subjective experience of individuals against objects that are unclear and specific due to anticipation of danger that allows individuals to take action to deal with threats. Many clients who are victims of bullying experience an anxiety disorder so that appropriate nursing care is needed for handling it. Research method uses a case study with 2 subjects according to inclusive criteria and the research instruments used are interviews, observation, and documentation. The results of the assessment in subject 1 often feel anxious and afraid when meeting with people who usually bully, the results of the Anxiety Sensitivity Index obtained moderate anxiety (51). Subject 2 often feels anxious and useless to others, the results of the Anxiety Sensitivity Index obtained low anxiety (92). The implementation for subject 1 is progressive muscle relaxation while in subject 2 is deep breath relaxation. The evaluation obtained in both subjects is that the client's anxiety is reduced, the client is more confident and the results of the Anxiety Sensitivity Index in both subjects show an increase. It is recommended for research subjects to be more courageous to tell stories and report if they receive bullying and for schools to pay more attention to the mental health of their students to prevent bullying from occurring again. For future researchers, it is recommended to examine more deeply related to the sources of coping involved such as family, friend, and community support.